A review of the combustion and emissions properties of advanced transportation biofuels and their impact on existing and future engines. (February 2015) - Bergthorson, Jeffrey M.; Thomson, Murray J.
Abstract: The fundamental combustion and emissions properties of advanced biofuels are reviewed, and their impact on engine performance is discussed, in order to guide the selection of optimal conversion routes for obtaining desired fuel combustion properties. Advanced biofuels from second- and third-generation feedstocks can result in significantly reduced life-cycle greenhouse-gas emissions, compared to traditional fossil fuels or first-generation biofuels from food-based feedstocks. These advanced biofuels include alcohols, biodiesel, or synthetic hydrocarbons obtained either from hydrotreatment of oxygenated biofuels or from Fischer–Tropsch synthesis. The engine performance and exhaust pollutant emissions of advanced biofuels are linked to their fundamental combustion properties, which can be modeled using combustion chemical-kinetic mechanisms and surrogate fuel blends. In general, first-generation or advanced biofuels perform well in existing combustion engines, either as blend additives with petro-fuels or as pure "drop-in" replacements. Generally, oxygenated biofuels produce lower intrinsic nitric-oxide and soot emissions than hydrocarbon fuels in fundamental experiments, but engine-test results can be complicated by multiple factors. In order to reduce engine emissions and improve fuel efficiency, several novel technologies, including engines and fuel cells, are being developed. The future fuel requirements for a selection of such novel power-generation technologies, along with their potential performance improvements over existing technologies, are discussed. The trend in the biofuels and transportation industries appears to be moving towards drop-in fuels that require little changes in vehicle or fueling infrastructure, but this comes at a cost of reduced life-cycle efficiencies for the overall alternative-fuel production and utilization system. In the future, fuel-flexible, high-efficiency, and ultra-low-emissions heat-engine and fuel-cell technologies promise to enable consumers to switch to the lowest-cost and cleanest fuel available in their market at any given time. This would also enable society as a whole to maximize its global level of transportation activity, while maintaining urban air quality, within an energy- and carbon-constrained world.